Findings in cattle consigned to Victorian knackeries between 2009 and 2018. Issue 8 (12th May 2020) - Gibney, JG; Pefanis, SM; Jeffers, MJ; Suter, RJ; Hunnam, JC
Abstract : Objective: To describe the causes of death or culling in cattle in Victoria, Australia, through surveillance at knackeries. Methods: Data were collected from 2797 adult cattle consigned to four Victorian knackeries over a 10‐year period (2009‐2018, inclusive). Cattle were sampled either at the point of collection or at a knackery. A single best‐fit diagnosis was assigned to each case to describe the cause of loss. Results: Sampled cattle were predominantly female dairy cattle originating from the three main dairying regions in Victoria. The most commonly diagnosed conditions were calving paralysis (6.8%), followed by mastitis (6.4%), hypocalcaemia (6.4%) and dystocia (5.9%). "Unknown" accounted for 24.2% of the cattle examined. Conclusion: This study provides a unique insight into the causes of death and culling in cattle consigned to Victorian knackeries. The periparturient period was identified as a high risk period for knackery consignment in adult female cattle.